Creative Behavior Mediates Learning Orientation, Knowledge Sharing, Motivation on Insurance (Study on 15 Big Insurance Companies in Indonesia) - Mochammad Isa Anshor; Anis Eliana; Falih Suaedi (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this research is to test and analyze the factors that affect the performance of insurance agents in this case insurance agents who are members of the Indonesian Life Insurance Association (AAJI) which are included in the 15 (fifteen) major insurance companies in Indonesia. This type of research is fundamental research or basic research, aiming to participate in the development of science. The method used is quantitative method with a total sample of 220 insurance agents. The analytical technique used in this research is SEM AMOS. The results showed that learning orientation had a significant effect on creative behavior, learning orientation had a significant effect on insurance agent performance, knowledge sharing had a significant effect on creative behavior, knowledge sharing had a significant effect on insurance agent performance, motivation had a significant effect on creative behavior, motivation had a significant effect on performance insurance agents, and creative behavior has a significant effect on the performance of insurance agents.